2019
DOI: 10.1002/npr2.12080
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic function in the lateral hypothalamus regulates feeding behavior: Possible mediation via orexin

Abstract: Aim:The lateral hypothalamus (LH) is known as the hunger center, but the mechanisms through which the LH regulates food intake are unclear. Since GABA neurons are reported to project to the LH, the present study investigated the role of GABAergic function in the LH in the regulation of feeding behavior.Methods: GABA levels in the LH were measured by in vivo microdialysis. Food intake after drug injection into the LH was measured every 1 hour for 4 hours. The mRNA levels were measured using RT-PCR.Results: Food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In this experiment, we applied the system to modulate the feeding behavior of freely behaving mice by delivering the drug to the region of the brain related to feeding and correlate with the change in their neural activities. Previous studies have reported that GABAergic neurons in the lateral hypothalamus (LH) manage satiety, and a GABA A receptor agonist, muscimol, modulates the neural circuit related to the feeding behavior 35 . To modulate feeding behavior, we implanted the neural probe system in the LH of wild mice followed by restricted caloric intake for 1 week after recovery.…”
Section: Resultsmentioning
confidence: 99%
“…In this experiment, we applied the system to modulate the feeding behavior of freely behaving mice by delivering the drug to the region of the brain related to feeding and correlate with the change in their neural activities. Previous studies have reported that GABAergic neurons in the lateral hypothalamus (LH) manage satiety, and a GABA A receptor agonist, muscimol, modulates the neural circuit related to the feeding behavior 35 . To modulate feeding behavior, we implanted the neural probe system in the LH of wild mice followed by restricted caloric intake for 1 week after recovery.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that GABA neurons send projections to the lateral hypothalamus and that food intake increases the level of GABA in the same nucleus [128]. The administration of muscimol (GABA A receptor agonist) decreases hypothalamic prepro-orexin mRNA and blocks food consumption [128] (Table 5). It was also reported that food consumption activated the GABAergic function in the lateral hypothalamus [128].…”
Section: Gabamentioning
confidence: 99%
“…The administration of muscimol (GABA A receptor agonist) decreases hypothalamic prepro-orexin mRNA and blocks food consumption [128] (Table 5). It was also reported that food consumption activated the GABAergic function in the lateral hypothalamus [128]. This activation, via GABA A receptors, terminates feeding, and it seems that GABA decreases food intake by inhibiting orexinergic neurons located in the lateral hypothalamus [128] (Table 5).…”
Section: Gabamentioning
confidence: 99%
“…Hepatic mRNA levels were measured as described previously 3,16,[38][39][40] : the liver was collected 30 min after drug injections, then immediately frozen in liquid nitrogen and kept at -80 °C until use; total RNA was isolated from the liver using RNAiso Plus (Takara Bio, Shiga, Japan) and reverse-transcribed to cDNA using PrimeScript RT reagent Kit (Takara Bio); the primers were mixed with buffer, dNTP mix, DNA polymerase and ultrapure water, and cDNA was added to the mixture for each reaction 3,16,[38][39][40] . The primers were: G6Pase (forward: 5′-CGA CTC GCT ATC TCC AAG TGA-3′, reverse: 5′-GTT GAA CCA GTC TCC GAC CA-3′); PEPCK (forward: 5′-CAT ATG CTG ATC CTG GGC ATA AC-3′, reverse: 5′-CAA ACT TCA TCC AGG CAA TGT C-3′); β-actin (forward: 5′-CAT CCG TAA AGA CCT CTA TGC CAA C-3′, reverse: 5′-ATG GAG CCA CCG ATC CAC A-3′) 3 .…”
Section: Reverse Transcription Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…The primers were: G6Pase (forward: 5′-CGA CTC GCT ATC TCC AAG TGA-3′, reverse: 5′-GTT GAA CCA GTC TCC GAC CA-3′); PEPCK (forward: 5′-CAT ATG CTG ATC CTG GGC ATA AC-3′, reverse: 5′-CAA ACT TCA TCC AGG CAA TGT C-3′); β-actin (forward: 5′-CAT CCG TAA AGA CCT CTA TGC CAA C-3′, reverse: 5′-ATG GAG CCA CCG ATC CAC A-3′) 3 . PCR was conducted on a thermal cycler (TP650; Takara Bio) as follows: 94 °C for 4 min 30 s, followed by 33 cycles of denaturing at 94 °C for 30 s, annealing at 58 °C for 1 min, and extension at 72 °C for 1 min 3,16,[38][39][40] . The PCR products were analyzed by electrophoresis on 1.7% agarose gels; the gel was stained with ethidium bromide, photographed with UV transillumination and intensity of the band analyzed by computer-assisted densitometry using ImageJ image-analysis software; the value for each enzyme was normalized by the respective value for β-actin, intensities of the bands obtained from drug-treated mice were compared with those of vehicle-treated mice, and the percentage of control was quantified for each sample 3,16,[38][39][40] .…”
Section: Reverse Transcription Polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%